SMPDL3B Predicts Poor Prognosis and Contributes to Development of Acute Myeloid Leukemia - Qu, Huiqing; Zhu, Ye (Frontiers in Molecular Biosciences, 2021)
ABSTRACT：Background: Acute myeloid leukemia (AML), characterized by the low cure rate and high relapse, urgently needs novel diagnostic or prognostic biomarkers and potential therapeutic targets. Sphingomyelin Phosphodiesterase Acid Like 3B (SMPDL3B) as a negative regulator of Toll-like receptor signaling that plays important roles in the interface of membrane biology and innate immunity. However, the potential role of SMPDL3B in human cancer，especially in AML, is still unknown. Methods: The expression of SMPDL3B in AML samples was investigated through data collected from Gene Expression Omnibus (GEO). Association between SMPDL3B expression and clinicopathologic characteristics was analyzed with the chi-square test. Survival curves were calculated by the Kaplan–Meier method. Cox univariate and multivariate analyses were used to detect risk factors for overall survival. The biological functions of SMPDL3B in human AML were investigated both in vitro and in vivo. Results: Expression of SMPDL3B mRNA was significantly up-regulated in human AML samples and closely correlated to cytogenetics risk and karyotypes. Elevated expression of SMPDL3B was associated with poor overall survival, and emerged as an independent predictor for poor overall survival in human AML. Blocked of SMPDL3B expression inhibited AML cells growth both in vitro and in vivo via promoting cell apoptosis. Conclusions: Taken together, our results demonstrate that SMPDL3B could be used as an efficient prognostic biomarker and represent a potential therapeutic target for human AML.